Examining the Legality of Adultery Restrictions for Laborers: A Study in Employment Law - Farid, M. Lutfi Rizal; Ikhsan, Muhammad Khananul; Putra, Calvin Anthony (Jurnal Hukum Magnum Opus, 2024)
The research aims to analyze and propose recommendations concerning regulations prohibiting acts of infidelity committed by workers/laborers from the perspective of labor law. Unlike labor laws and regulations, which do not specifically address the prohibition of acts of infidelity, autonomous rules can address such provisions. This study employs a normative legal research methodology, utilizing both statutory and conceptual approaches. Primary and secondary legal materials serve as the basis for analysis. Findings indicate that provisions prohibiting acts of infidelity for workers/laborers can be integrated into autonomous principles without contravening existing laws and regulations. Furthermore, acts of infidelity may also fall under the purview of urgent offenses or criminal acts. The inclusion of such prohibitions in autonomous rules is not indicative of bad faith on the part of employers seeking to expedite termination of employment relations. Rather, it serves as a preventive measure against violations of laws, regulations, and ethical standards by workers/laborers. Regarding dispute resolution, termination of employment cannot be immediate in cases related to allegations of infidelity. Instead, due process must be followed to ascertain the veracity of such accusations and determine the culpability of the worker/laborer involved.